Implementation of Regulation of the Minister of Religious Affairs Number 20 of 2019 in the Practice of Changing the Biodata of the Marriage Certificate in Krian District - Thoriq M Firdaus; Abdullah Taufik; Muhammad Fajar Sidiq Widodo (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Purpose – This study aims to determine the practice of resolving changes in the biodata of marriage certificates at the Office of Religious Affairs (KUA) in the KUA of Krian District, Sidoarjo Regency, besides that the author also wants to know what obstacles occur in the settlement of changes in marriage certificates after the issuance of Regulation of the Minister of Religion No. 20 of 2019 concerning Marriage Registration. Methods – This research uses empirical juridical methods with a socio-legal approach. And in collecting data the author uses interview techniques, documentation, observation, literature study and internet searching. Data analysis is done in three ways, namely data reduction, data presentation, and drawing conclusions or verification.. Findings – The results showed that in the practice of resolving changes in the biodata of marriage certificates at the KUA Krian District, Sidoarjo Regency was not fully in accordance with the Regulation of the Minister of Religion No. 20 of 2019 concerning Marriage Registration. This is due to the absence of the latest birth certificate and certificate issued by the population and civil registration office as the basis for the KUA in changing the biodata of the marriage certificate. Research implications/limitations – Thus, based on the above conclusions, the authors recommend as a form of evaluation for related parties regarding changes in the biodata of the marriage certificate at the KUA Krian District. Originality/value – This research is important because the implementation of minister of religion regulation number 20 of 2019 at the religious affairs office has not been maximised. Therefore, the existence of this research is expected to be a practical reference for other KUAs by making the practice of changing the biodata of the marriage certificate of the Krian District KUA the object of study.